Forensic Investigation in SQL Server Database Using Temporal Tables & Extended Events Artifacts - Shadi Khaled A. Zakarneh (Universitas Sanata Dharma, 2023)
Different Database management systems (DBMS) were developed and introduced to store and manipulate data. Microsoft SQL (MSSQL) Server one of the most popular relational DBMS used for large databases. With the increasing use of databases, intentional and unintentional accidents on databases are increasing dramatically. Therefore, there is a great need to develop database forensic investigation (DBFI) tools and models. The temporal table is a new feature introduced with MSSQL server 2012 for track changes, database audit, data loss protection, and data recovery. In addition, the extended events another new feature introduced with MSSQL server 2008 for database performance troubleshooting. This study focused on DBFI in the MSSQL server using temporal tables and extended events artifacts. The experiment is conducted and the results have presented the use of the temporal tables and extended events artifacts in analyzing and determining the internal unauthorized modification on the database.